Numerical Simulation of Cholera Epidemic Model with Quarantine - Trisilowati Trisilowati; Ari Andari; Muhammad Abdurrahman Rois; Mohamad Hasyim Muzaqi (Telematika, 2021)
Cholera is an acute diarrheal disease that spread quickly in an unsanitary environment, and one of its control measures is employing quarantine. Therefore, this research aims to construct a model for the spread of SIRQB-type (susceptibles, infective, recovered, quarantine, bacteria) infectious diseases through a nonlinear differential equation approach. Furthermore, the equilibrium points condition and their stability were investigated using the standard dynamical analysis method. The results show two points of equilibrium: the disease-free, which always exists and is unstable, and the endemic, which is stable and exists under certain conditions. Also, the simulation carried out support the analysis results, and it shows that the rate of quarantine affects the spread of the infected subpopulation.